Mutu gizi dan daya terima es krim indeks glikemik rendah berbahan polisakarida larut air umbi gembili (Dioscorea esculenta) dan tepung ubi jalar ungu (Ipomoea Batatas L. Poir) - I Komang Suwita; Juin Hadisuyitno (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Background: The development of ice cream products by adding certain ingredients such as fiber can improve the quality of the product as a healthy food. Research pur¬poses: This study aims to analyze the effect of the water-soluble polysaccharide substi¬tution of gembili tubers with purple sweet potato flour on nutritional quality, physico-chemical properties, and organoleptic quality of ice cream. Method: This study used a completely randomized design (CRD), consists of four levels, namely control (P0) and water-soluble polysaccharide substitution treatment of gembili tubers with purple sweet potato flour; P1, P2, P3 with three replications each. Results and Discussion: The results of the research on ice cream substitution of water-soluble polysaccharide of gembili tubers with purple sweet potato flour showed a significant effect (P <0.05) on ash, protein, and carbohydrate content, and there was no significant effect on mois¬ture content and energy value. Caused increase in the volume of ice cream products at all levels of substitution treatment (P0, P1, P2, and P3). P0 was the ice cream prod¬uct with the highest increase (2,057 times, and then P3 (1,933 times). In the treatment of ice cream, water-soluble polysaccharide substitution of gembili tubers with purple sweet potato flour, there was a change in the ash, protein, fat, carbohydrate content. energy and increased fiber content. Conclusion: The best level of treatment based on the effectiveness index is P3.